Efficacy of retreatment with immunomodulatory drugs and proteasome inhibitors following daratumumab monotherapy in relapsed and refractory multiple myeloma patients. (6th August 2018) - Oostvogels, Rimke; Jak, Margot; Raymakers, Reinier; Mous, Rogier; Minnema, Monique C.
Summary: This single‐centre retrospective observational study analysed the efficacy of retreatment with immunomodulatory agents (IMiDs) and proteasome inhibitors (PIs) after treatment with daratumumab monotherapy in patients with relapsed and/or refractory multiple myeloma (RRMM). In total 55 patients were treated with daratumumab monotherapy between 2010 and 2017. From this group 29 (53%) IMiD‐refractory patients were retreated with an IMiD after daratumumab and 6 (11%) PI‐refractory patients were retreated with a PI‐based regimen. For the IMiD‐refractory patients the overall response rate (ORR) was 52% (15/29 patients, partial response or better) upon IMiD retreatment, whereas the ORR to PI retreatment was 67% (4/6 patients) in the PI‐refractory group. The immunomodulatory effects of daratumumab may play a role in these high response rates in previously refractory patients. Due to the >6 month‐long persistence of daratumumab in the plasma the subsequent therapies can effectively be considered as combination therapy. Furthermore, the excellent tolerability of daratumumab treatment may enable patients to recover from prior lines of treatment and receive full dosing of subsequent therapies. In conclusion, a high proportion of RRMM patients benefitted from retreatment with IMiDs and PIs after daratumumab treatment. These retreatment options should therefore be explored in RRMM patients progressing on daratumumab monotherapy.